Physiological parameters and CO2 efflux in areas cultivated with beans and maize - Pereira, Alécio Rodrigues e (2024)
The present study has the objective of estimating the of carbon dioxide efflux (CO2) in an area cultivated with bean and maize. The experiment was conducted at the experimental irrigation and drainage unit of the Department of Agricultural Engineering, located at the Federal University of Viçosa. The crops used were Ouro of Mata bean and maize (BM270) during two cultivation cycles as well as carioca bean (VC25) in a single cropping cycle. CO2 efflux was measured using an infrared gas analyzer (IRGA), attached to the LC-PRO+ portable system, manufactured by the company ADC BIO Scientific. To read soil respiration and the ecophysiological parameters, IRGA was coupled to the soil and photosynthesis chamber, respectively. The ecophysiological parameters photosynthesis (A), stomatal conductance (gs), transpiration (E), internal carbon concentration (Ci), instantaneous water use efficiency (EiUA) and instantaneous carboxylation efficiency (EiC) were monitored. In the area cultivated with Ouro of Mata bean the mean soil respiration during the two crop cycles was 1.02 and 1.65 µmol m-2 s-1, respectively. For the maize area between 1.24 and 1.25 µmol m-2 s-1, in the first and second cycle, respectively. For the carioca bean crop the mean for the entire crop cycle were 1.44 µmol m-2 s-1. For Ouro of Mata bean the ecophysiological parameters In the first cultivation cycle the mean values of 27.97 µmol m-2 s-1 (A), 0.61 mol of H2O m-2 s-1 (gs), 5.93 mol of H2O m-2 s-1 (E), 297.09 µmol mol-1 (Ci), 4.60 µmol mol-1 of H2O (EiUA) and 0.095 mol m-2 s-1 (EiC) and in the second cycle 25.74 µmol m-2 s-1 (A) , 0.28 mol of H2O m-2 s-1 (gs), 4.38 mol of H2O m-2 s-1 (E), 293.30 µmol mol-1 (Ci), 5.87 µmol mol-1 of H2O (EiUA) and 0.091 mol m-2 s-1 (EiC). In the first maize crop cycle the following values were observed 52.07 µmol.m-2 s-1 (A), 0.52 mol of H2O m-2 s-1 (gs), 7.68 mol of H2O m-2 s-1 (E), 211.95 µmol mol-1 (Ci), 6.78 µmol mol-1 of H2O (EiUA) and 0.245 mol m-2 s-1 (EiC), and in the second cycle 26.85 µmol.m-2 s-1 (A), 0.30 mol of H2O m-2 s-1 (gs), 3.66 mol of H2O m-2 s-1 (E), 222.05 µmol mol-1 (Ci), 7.96 µmol mol-1 of H2O (EiUA) and 0.130 mol m-2 s-1 (EiC). For the Carioca bean crop, the mean values of 23 µmol m-2 s- (A), 0.30 mol of H2O m-2 s-1 (gs), 3.78 mol of H2O m-2 s-1 (E), 311.04 µmol mol-1 (Ci), 6.02 µmol mol-1 of H2O (EiUA) and 0.080 mol m-2 s-1 (EiC). Keywords: soil respiration; photosynthesis; bean; maize; co2.